Intrathecal liposomal cytarabine plus systemic therapy versus systemic chemotherapy alone for newly diagnosed leptomeningeal metastasis from breast cancer. Issue 4 (22nd October 2019) - Le Rhun, Emilie; Wallet, Jennifer; Mailliez, Audrey; Le Deley, Marie Cecile; Rodrigues, Isabelle; Boulanger, Thomas; Lorgis, Veronique; Barrière, Jerome; Robin, Yves Marie; Weller, Michael; Bonneterre, Jacques
Abstract: Background: DEPOSEIN (NCT01645839) was a randomized open-label phase III study to explore the role of intrathecal chemotherapy in patients with newly diagnosed leptomeningeal metastasis (LM), a common manifestation of breast cancer. Methods: Patients with newly diagnosed LM defined by tumor cells in the cerebrospinal fluid or combination of clinical and neuroimaging signs of LM were randomized to receive systemic therapy alone (control group) or systemic therapy plus intrathecal liposomal cytarabine (experimental group). Progression-free survival related to LM (LM-PFS) was the primary endpoint. Results: Thirty-seven and 36 patients were assigned to the control and the experimental groups. Median number of liposomal cytarabine injections in the experimental group was 5 (range 1–20). Focal radiotherapy was performed in 6 (16%) and 3 (8%) patients in the control and experimental groups. In the intent-to-treat population, median LM-PFS was 2.2 months (95% CI: 1.3–3.1) in the control versus 3.8 months (95% CI: 2.3–6.8) in the experimental group (hazard ratio 0.61, 95% CI: 0.38–0.98) ( P = 0.04). Seventy-one patients have died. Median overall survival was 4.0 months (95% CI: 2.2–6.3) in the control versus 7.3 months (95% CI: 3.9–9.6) in the experimental group (hazard ratio 0.85, 95% CI: 0.53–1.36) ( P = 0.51). Serious adverse events were reported in 22 and 30 patients, respectively. Quality of life until progression did not differ between groups. Conclusion: The addition of intrathecal liposomal cytarabine to systemic treatment improves LM-related PFS. Confirmatory trials with optimized patient selection criteria and more active drugs may be required to demonstrate a survival benefit from intrathecal pharmacotherapy.